Water saving with a PLC based adaptive irrigation system - Shahidian, S. (2009)
Irrigation is presently the main user of world´s fresh water. Most of it goes to irrigating small plots where it is not feasible to implement full-scale Evapotranspiration based irrigation controllers. The dramatic development of Programmable Logic Controllers, PLCs, and their rather affordable price has made it possible to use them as stand-alone irrigation controllers. In this paper a PLC is used to adapt the daily irrigation amount to actual ETc, using a Hargreaves-Samani type equation. Once the ETc is calculated, then the PLC manages the irrigation according to the specifications given by the farmer. First year results indicate an 8% saving in irrigation water.